M6A methylation potentiates cytosolic dsDNA recognition in a sequence-specific manner. Issue 3 (10th March 2021) - Balzarolo, Melania; Engels, Sander; de Jong, Anja J.; Franke, Katka; van den Berg, Timo K.; Gulen, Muhammet F.; Ablasser, Andrea; Janssen, Edith M.; van Steensel, Bas; Wolkers, Monika C.
Abstract : Abstract : Nucleic acid sensing through pattern recognition receptors is critical for immune recognition of microbial infections. Microbial DNA is frequently methylated at the N 6 position of adenines (m6A), a modification that is rare in mammalian host DNA. We show here how that m6A methylation of 5′-GATC-3′ motifs augments the immunogenicity of synthetic double-stranded (ds)DNA in murine macrophages and dendritic cells. Transfection with m6A-methylated DNA increased the expression of the activation markers CD69 and CD86, and of Ifnβ, iNos and Cxcl10 mRNA. Similar to unmethylated cytosolic dsDNA, recognition of m6A DNA occurs independently of TLR and RIG-I signalling, but requires the two key mediators of cytosolic DNA sensing, STING and cGAS. Intriguingly, the response to m6A DNA is sequence-specific. m6A is immunostimulatory in some motifs, but immunosuppressive in others, a feature that is conserved between mouse and human macrophages. In conclusion, epigenetic alterations of DNA depend on the context of the sequence and are differentially perceived by innate cells, a feature that could potentially be used for the design of immune-modulating therapeutics.